Enzymes, Dentinogenesis and Dental Caries: a Literature Review - Markku Larmas; George K. B. Sándor (eJournal of Oral Maxillofacial Research, 2014)
Objectives: Search in PubMed with keywords “enzymes, dentinogenesis, and dental caries” revealed only 4 items, but when combined with “enzymes, osteogenesis, and osteoporosis” as high as 404 items resulted. Dental caries was associated with an order of magnitude fewer studies than the chronic bone disease, osteoporosis. This observation motivated this review.